Content Analysis of Inquiry and Authentic Assessment in 8th Grade Science Subject Textbook (Unnes Science Education Journal, 2022)
This study aims to determine the content of inquiry and authentic assessment components in the analyzed science textbooks. The type of research approach used in this research was qualitative research with descriptive methods in the form of document analysis of Natural Science textbooks for 8th grade Junior High School published by the Ministry of Education and Culture and another book from non-ministerial publisher. The result showed that in the aspect of inquiry, the component with the highest number of findings was in the data collecting component, namely 61 findings in book I and 59 findings in book II. Meanwhile, the the lowest number of findings was the proposing hypothesis with 0 finding in the both books. In the authentic assessment aspect, the component with the highest number of findings lies in the physical context component, namely 33 findings in book I and the assessment task component with a total of 32 findings in book II. Meanwhile, the lowest number of findings in the two books was found in the assessment criteria component with 11 findings in book I and 5 findings in book II.